Effectiveness Analysis Of Electronic Medical Record Implementation At Wangaya Regional General Hospital, Denpasar - Sutama, Kompiang Gede; Dewi, Nyoman Diah Utari; Widnyani, Ida Ayu Putu Sri (Jurnal Scientia, 2024)
The implementation of Electronic Medical Records (RME) in hospitals is an important effort to improve the efficiency of public administration and the quality of health services. However, in practice, the implementation of RME in regional hospitals, such as Wangaya Regional Hospital, Denpasar, still faces various challenges, including limited technological infrastructure, resistance from medical personnel, and unclear regulations. This research aims to analyze the effectiveness of implementing RME at Wangaya Regional Hospital from a public administration perspective. The method used is a literature review which summarizes various research in the last five years related to the implementation of RME in hospitals. The research results show that RME has the potential to increase administrative efficiency, transparency and accountability in medical data management, as well as speed up clinical decision making. However, the main challenges are still related to the lack of adequate technological infrastructure and the need for training for medical personnel. Recommended solutions include improving digital infrastructure, providing ongoing training for medical personnel, and strengthening regulations and policies regarding the use of RME. Effective implementation of RME in government hospitals will contribute significantly to improving the quality of health services in Indonesia.